2019
DOI: 10.3389/fmicb.2019.02004
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, Diet, and Developmental Stage Contribute to the Structuring of Gut-Associated Bacterial Communities in Tephritid Pest Species

Abstract: Insect-symbiont interactions are receiving much attention in the last years. Symbiotic communities have been found to influence a variety of parameters regarding their host physiology and fitness. Gut symbiotic communities can be dynamic, changing through time and developmental stage. Whether these changes represent real differential needs and preferential relationships has not been addressed yet. In this study, we characterized the structure of symbiotic communities of five laboratory populations that represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
33
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 68 publications
9
33
3
Order By: Relevance
“…Differences between microbiome profiles can be related to life history traits and environmental factors including life stage ( Lauzon et al, 2009 ; Andongma et al, 2015 ), diet ( Santo Domingo et al, 1998 ; De Vries et al, 2004 ; Colman et al, 2012 ; Morrow et al, 2015 ), or technical artifacts ( De Cock et al, 2019 ). Consistent with what has been reported in other studies on frugivorous tephritids ( Thaochan et al, 2010 ; Wang et al, 2011 ; Andongma et al, 2015 ; Morrow et al, 2015 ; Augustinos et al, 2019 ), the gut microbiome profiles of third instar larvae of the ten fruit fly species targeted by the present study were mainly composed of Proteobacteria and Firmicutes which together represented more than 98.49% of reads in all tephritid species targeted. Andongma et al (2015) suggested that Proteobacteria might be the most abundant phylum in earlier developmental stages of Bactrocera , while Firmicutes the most abundant in adult stages, possibly as a result of changes in habitat and diet.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Differences between microbiome profiles can be related to life history traits and environmental factors including life stage ( Lauzon et al, 2009 ; Andongma et al, 2015 ), diet ( Santo Domingo et al, 1998 ; De Vries et al, 2004 ; Colman et al, 2012 ; Morrow et al, 2015 ), or technical artifacts ( De Cock et al, 2019 ). Consistent with what has been reported in other studies on frugivorous tephritids ( Thaochan et al, 2010 ; Wang et al, 2011 ; Andongma et al, 2015 ; Morrow et al, 2015 ; Augustinos et al, 2019 ), the gut microbiome profiles of third instar larvae of the ten fruit fly species targeted by the present study were mainly composed of Proteobacteria and Firmicutes which together represented more than 98.49% of reads in all tephritid species targeted. Andongma et al (2015) suggested that Proteobacteria might be the most abundant phylum in earlier developmental stages of Bactrocera , while Firmicutes the most abundant in adult stages, possibly as a result of changes in habitat and diet.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the currently available research on tephritid gut microbiomics focuses on fruit fly laboratory populations (i.e., fed with artificial diets) and often aims at investigating the optimal rearing conditions for species of interest for the sterile insect technique (SIT) ( Augustinos et al, 2015 , 2019 ; Kyritsis et al, 2017 , 2019 ; Asimakis et al, 2019 ) while the composition and levels of variability of microbiome profiles of wild tephritid flies are far less known.…”
Section: Introductionmentioning
confidence: 99%
“…Other less abundant genera such as Enterobacter sp., Providencia sp., Klebsiella sp. (Manousis & Ellar, 1988; Augustinos et al, 2019; Koskinioti et al, 2019), Acetobacter tropicalis (Kounatidis et al, 2009), Pantoea sp. (Ben‐Yosef et al, 2015; Koskinioti et al, 2019), Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…(Blow et al, 2019), and Morganella sp. (Augustinos et al, 2019) have also been identified in the olive fruit fly gut but their role in the fly’s biology is not fully known yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation